KAJIAN MACAM PUPUK HAYATI TERHADAP INTENSITAS PENYAKIT BERCAK DAUN Cercospora sp PADA TANAMAN JAGUNG HITAM - Nining Saputri; Sartono Joko Santosa; Saiful Bahri (Innofarm:Jurnal Inovasi Pertanian, 2020)
This study is titled Study of Biological Fertilizers on the intensity of Leaf Spots (Cercospora sp.) On Black Corn (Black Aztec) with the aim to study the types of biological fertilizers on the intensity of Cercospora sp. which began on November 9, 2019, in Jembangan Village, Gagaksipat Village, Ngemplak District, Boyolali District, Central Java, with a height of 150m (asl). This study uses a single factor Complete Randomized Block Design (RCBD) consisting of 10 treatments and 3 replications. The data from the results of this study were analyzed with the Duncan at the 5% level. The parameters observed include: intensity of leaf spot disease, weight of cob with corn husk per plant (gram), weight of cob without corn husk per plant (gram), weight of 100 corn seeds (gram). The results showed that: (1) Symptoms of leaf spot disease appear evenly on all biological fertilizers, symptoms of disease attack began to appear at the age of 30 days after planting. (2) In the treatment of biological fertilizer Megharizo on black corn concertration 10 ml/1,2 l (B2) can reduce the intensity of leaf spot disease. (3) The application of biological fertilizer from three doses has not been able to increase the yield of black corn to the weight of corn with corn husk, weight of corn without corn husk, and weight of 100 seeds.